Finnish students' reasons for their achievement in classroom activities: focus on features that support self-regulated learning. Issue 1 (2nd January 2017) - Mykkänen, Arttu; Perry, Nancy; Järvelä, Sanna
Abstract : The aim of this study was to investigate how finnish students explain factors that contribute to their achievement in classroom learning activities and whether these factors are related to support of self-regulated learning (SRL) in classroom. Over seven weeks, 24 primary school students were videotaped during their typical classroom activities in 28 lessons to capture moments when they succeeded in learning tasks. From the video observations, 62 episodes were edited and used in stimulated recall interviews in which students were asked to report the reasons they related to their achievement in learning situations. Data-driven content analysis was used to analyse the open-ended interview data. The video observation data were analysed and sorted into theory-driven categories in order to find out how SRL was supported in classrooms. The results showed that students describe achievement through the actions that they took in the learning situations, such as being able accomplish the task. The reasons given for their achievement dealt with ability to accomplish the tasks or doing academic activities in order to achieve in the task. Furthermore, the students recognised classroom activities that support SRL, acknowledging their contribution to their achievement, mostly through the support that they received from their teachers and peers.